Le découpage électoral au Liban : une lecture géopolitique de la loi de 2000 - Ali El Samad (L'Espace Politique)
The electoral law is very important in Lebanon, however it is not the choice of the electoral system (majority or proportional) that is the most significant issue but the nature and the geographical and administrative dimensions of the electoral district. The character of the community of voters is one of the most influential factors in defining the electoral district. In principal, an « ideal» electoral law should be equitable (between communities), egalitarian (number of votes) and stable (for multiple legislative elections). However these criteria remain difficult to satisfy due to different community specifics and the internal political context. This article aims to clarify the principles behind the definition of electoral boundaries and its importance in the political and institutional system, and the importance of this in the evolution of democratic values in Lebanon. Do these electoral districts respect the territorial realities and the geographic distribution of the Lebanese communities? What relations exist between the political electoral boundaries and the administrative boundaries? Two successive legislative elections were organised in 2000 and in 2005 based on the electoral law of 2000. The objective of this article is to present how this electoral law violated the internal administrative borders in Lebanon -the law does not reflect the representation of the population, in fact it exacerbates community tensions and presents an obstacle to territorial cohesion and national unity. Using a geo-political approach, we will propose some criteria to modify to the geographical and political boundaries of the electoral districts.